ChemInform Abstract: Recent Advances in Mn‐Based Oxides as Anode Materials for Lithium Ion Batteries. Issue 39 (23rd September 2014) - Deng, Yuanfu; Wan, Lina; Xie, Ye; Qin, Xusong; Chen, Guohua
Abstract Review: 155 refs.